2021
DOI: 10.1002/cbin.11588
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTTIP inhibits cell pyroptosis by targeting miR‐148a‐3p/AKT2 axis in ovarian cancer

Abstract: Long noncoding RNA HOTTIP is a crucial regulator in multiple types of cancer, including ovarian cancer (OC). However, the biological roles and underlying mechanisms of HOTTIP in OC have rarely been studied. Hence, this study aimed to investigate the functional correlation between HOTTIP and pyroptosis in OC progression. The expression of HOTTIP in OC tissues and cell lines was characterized by quantitative real‐time PCR. Cell proliferation was evaluated using Cell Counting Kit‐8 and clone formation assays. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…Several reports have demonstrated that lncRNAs regulate the mediators of pyroptosis, including NLR family pyrin domain containing 1 (NLRP1) ( 26 ), NLR family pyrin domain containing 3 (NLRP3) ( 27 ), Casp1 ( 28 ) and Casp3 ( 29 ). Nevertheless, the non-coding RNAs that regulate GSDMs, the key execution proteins of pyroptosis have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that lncRNAs regulate the mediators of pyroptosis, including NLR family pyrin domain containing 1 (NLRP1) ( 26 ), NLR family pyrin domain containing 3 (NLRP3) ( 27 ), Casp1 ( 28 ) and Casp3 ( 29 ). Nevertheless, the non-coding RNAs that regulate GSDMs, the key execution proteins of pyroptosis have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2021) revealed that lncRNA XIST promoted pyroptosis through the XIST/miR-150-5p/c-Fos axis, and Wan et al (2020) discovered that lncRNA-H19 significantly promoted NLRP3/6 inflammasome imbalance and induced pyroptosis of microgliocyte. Furthermore, Tan et al (2021) found that LncRNA HOTTIP could inhibit pyroptosis of ovarian cancer cells by targeting the miR-148a-3p/AKT2 axis. However, there are limited studies focusing on pyroptosis-associated lncRNAs in BC.…”
Section: Introductionmentioning
confidence: 99%
“… 11 A study showed that lncRNA HOTTIP holds up ovarian cancer cell pyroptosis by modulating the miR-148a-3p/AKT2 signaling pathway. 12 In addition, another work showed that lncRNA ADAMTS9-AS2 induces pyroptotic cell death and strengthens gastric cancer cells’ sensitivity to cisplatin. 13 Moreover, downregulation of lncRNA XIST restrained non-small cell lung cancer multiplication through irritating pyroptosis.…”
Section: Introductionmentioning
confidence: 99%